The Exploring Between Theological Thinking And Education On Abd.Qahhar Mudzakkar - et. al., Muhammad Hasbi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Revealing the history of the struggle for the establishment of an Islamic State has appeared for a long time to accompany the journey of the Indonesian nation. One of them is Abd. Qahhar Mudzakkar, a Muslim fighter from South Sulawesi, was fighting for Islam as an ideology through the formation of an Islamic stated. Anyone who is different will be radically opposed, including the legitimate government of the Soekarno era. Apart from his struggles, there are thought factors that dominate Qahhar Mudzakkar's way of thinking, placing Islam as an ideology through the formation of an Islamic State. This way of thinking is also inseparable from social and cultural spaces, especially when the Qahhar Mudzakkar education process takes place, forming a radical understanding and violent action on the basis of Islam, to be precise the struggle to form an Islamic stated. From a theological point of view, Qahhar Mudzakkar's Islamic ideology is based on his understanding of the Qur'an and hadith, especially as its theological basis. For this reason, when observed from the historical context of kalam, the Islamic ideology that Qahhar Mudzakkar was fighting for has a geneological affinity with the Khawarij group; an Islamic group that has always acted harshly on different Muslims; from accusing infidels to justifying all forms of violence and killing those who are different. To strengthen his Islamic ideological base, Qahhar Mudzakkar uses educational institutions. This approach is considered important because in the world of education there is a process of doctrinal indoctrinization, including teaching to be involved in the struggle of Qahhar Mudzakkar. The combination of strengthening thought and regeneration is seen as strengthening Qahhar Mudzakkar's struggle to establish an Islamic stated, which often uses violence against different methods. With the strong theological basis on the one hand and the inclusion of ideology through education on the other side, Qahhar Mudzakkar's army was growing and maturing in many ways. Therefore, the Republic of Indonesia army was also bothered to crush the DI / TII movement commanded by Qahhar Mudzakkar, with the basic assumption that the movement was a rebel.